2021
DOI: 10.1021/acs.chemmater.1c00098
|View full text |Cite
|
Sign up to set email alerts
|

Dual Passivation of SnO2 by Tetramethylammonium Chloride for High-Performance CsPbI2Br-Based Inorganic Perovskite Solar Cells

Abstract: Here, the modification of the SnO2 electron transport layer (ETL) by tetramethylammonium chloride (TMACl) is described. The theoretical and experimental studies in this work demonstrate that TMA and Cl ions complementarily passivate the oxygen vacancies on the surface of SnO2 ETL, while TMACl passivation also contributes to increase the conduction band edge of SnO2 by reducing the work function. As a result, the charge carrier recombination and electron transfer/extraction behaviors at the interface of CsPbI2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 40 publications
(59 reference statements)
0
40
0
Order By: Relevance
“…Three peaks at 528.2, 528.8, and 529.8 eV represent the lattice oxygen (O L ), the vacancy oxygen (O V ), and the chemisorbed oxygen (O C ), respectively. In specific, the peak at the lowest binding energy (O L ) is associated with the lattice oxygen atoms (O 2− ) in a fully coordinated SnO 2 with the Sn 4+ ions while the highest binding energy peak is the loosely adsorbed dissociated oxygen or hydroxyl group at the surface (O C ) 28 . The binding energy peak at the middle range (O V ) can thus be interpreted to the oxygen attributed to vacancies in the lattice matrix of SnO 2 (O − , O 2− ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three peaks at 528.2, 528.8, and 529.8 eV represent the lattice oxygen (O L ), the vacancy oxygen (O V ), and the chemisorbed oxygen (O C ), respectively. In specific, the peak at the lowest binding energy (O L ) is associated with the lattice oxygen atoms (O 2− ) in a fully coordinated SnO 2 with the Sn 4+ ions while the highest binding energy peak is the loosely adsorbed dissociated oxygen or hydroxyl group at the surface (O C ) 28 . The binding energy peak at the middle range (O V ) can thus be interpreted to the oxygen attributed to vacancies in the lattice matrix of SnO 2 (O − , O 2− ).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the materials engineering of the perovskite absorber layer, modification of interfacial charge transport layers also plays an important role in determining the charge extraction and recombination kinetics of PSCs 24‐28 . In particular, the moisture/oxygen permeability of the interfaces of the device can cause serious degradation of PSCs, so suitable selection of the optimal interfacial layers is critical to increasing PCE and stability of PSCs, simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…To passivate the oxygen vacancies on the SnO 2 ETL for n‐i‐p PALCs, Parida et al [61] . used tetramethylammonium chloride (TMACl).…”
Section: Research Directions and Progress For High‐performance Palcsmentioning
confidence: 99%
“…To passivate the oxygen vacancies on the SnO 2 ETL for n-i-p PALCs, Parida et al [61] used tetramethylammonium chloride (TMACl). They found that interfacial charge transfer and extraction in PALCs was enhanced by minimizing losses through charge carrier recombination after SnO 2 was treated with TAMCl.…”
Section: Engineering Interlayer Materials For Palcsmentioning
confidence: 99%
See 1 more Smart Citation